Energy Charge as an Indicator of Pexophagy in Pichia pastoris - Zhang, Jianguo; Liu, Taiyu (Frontiers in Microbiology, 2017)
Pichia pastoris is a good model for pexophagy research owing to its diverse pexophagy modes (macropexophagy and micropexophagy) exhibited during carbon-source shift from methanol to other carbon sources. The critical condition that triggers activation of macropexophagy and micropexophagy is important for clarifying the P. pastoris pexophagy mechanism and human peroxisomal disorders. In this study, the pexophagy modes of P. pastoris were confirmed by green fluorescent protein expression and alcohol oxidase and formate dehydrogenase activities. Furthermore, intracellular energy charge (EC) was found to be a determinant of pexophagy activation. During methanol induction, the EC was about 0.5. And the final EC value was related to the pexophagy mode when carbon source switched from methanol to others. Macropexophagy and micropexophagy occurred when the EC increased to 0.6–0.75 and above 0.75, respectively. Thus, different EC values were considered as the important factor to trigger different pexophagy modes in P. pastoris. The results obtained in this study could help in achieving better control of the pexophagy modes to study the pexophagy mechanism.